Balancing the competitive adsorption of NO and H2 on Pt sites for broadened H2-SCR window of Pt/zeolite-Zr0.5Ti0.5O2 composite catalysts - Yan Li; Yan Huang; Zhen Tian; Liuling Chen; Chengsong Huang; Jiayi Li; Yaoqiang Chen; Jianli Wang; Haidi Xu (Fuel, 2026)

Development and deployment of KASP markers for multiple alleles of Lr34 in wheat - Tilin Fang; Lei Lei; Genqiao Li; Carol Powers; Robert M. Hunger; Brett F. Carver; Liuling Yan (Theoretical and Applied Genetics, 2020)
Key message Heterogeneous Lr34 genes for leaf rust in winter wheat cultivar ‘Duster’ and KASP markers for allelic variation in exon 11 and exon 22 of Lr34. Abstract Wheat, Triticum aestivum (2 n = 6 x = 42, AABBDD), is a hexaploid species, and each of three homoeologous genomes A, B, and D should have one copy for a gene in its ancestral form if the gene has no duplication. Previously reported leaf rust resistance gene Lr34 has one copy on the short arm of chromosome 7D in hexaploid wheat, and allelic variation in Lr34 is in intron 4, exon 11, exon 12, or exon 22. In this study, we discovered that Oklahoma hard red winter wheat cultivar ‘Duster’ (PI 644,016) has two copies of the Lr34 gene, the resistance allele Lr34a and the susceptibility allele Lr34b . Both Lr34a and Lr34b were mapped in the same linkage group on chromosome 7D in a doubled-haploid population generated from a cross between Duster and a winter wheat cultivar ‘Billings’ which carries the susceptibility allele Lr34c . A chromosomal fragment including Lr34 and at least two neighboring genes on its proximal side but excluding genes on its distal side was duplicated in Duster. The Duster Lr34ab allele was associated with tip necrosis and increased resistance against leaf rust at adult plants in the Duster × Billings DH population tested in the field, demonstrating the function of the Duster Lr34ab allele in wheat. We have developed KASP markers for allelic variation in exon 11 and exon 22 of Lr34 in wheat. These markers can be utilized to accelerate the selection of Lr34 in wheat.

Duplicated, deleted and translocated VRN2 genes in hexaploid wheat - ChorTee Tan; Liuling Yan (Euphytica, 2016)

TaXA21-A1 on chromosome 5AL is associated with resistance to multiple pests in wheat - Meiyan Liu; Lei Lei; Carol Powers; Zhiyong Liu; Kimberly G. Campbell; Xianming Chen; Robert L. Bowden; Brett F. Carver; Liuling Yan (Theoretical and Applied Genetics, 2016)

QTL Mapping for Reproductive Maturity in Lowland Switchgrass Populations - Hongxu Dong; Shuiyi Thames; Linglong Liu; Michael W. Smith; Liuling Yan; Yanqi Wu (BioEnergy Research, 2015)

Increased copy number at the HvFT1 locus is associated with accelerated flowering time in barley - Rebecca Nitcher; Assaf Distelfeld; ChorTee Tan; Liuling Yan; Jorge Dubcovsky (Molecular Genetics and Genomics, 2013)

A single-nucleotide polymorphism that accounts for allelic variation in the Lr34 gene and leaf rust reaction in hard winter wheat - Shuanghe Cao; Brett F. Carver; Xinkai Zhu; Tilin Fang; Yihua Chen; Robert M. Hunger; Liuling Yan (Theoretical and Applied Genetics, 2010)

Genetic loci in the photoperiod pathway interactively modulate reproductive development of winter wheat - Shuwen Wang; Brett Carver; Liuling Yan (Theoretical and Applied Genetics, 2009)

Genetic loci associated with stem elongation and winter dormancy release in wheat - Yihua Chen; Brett F. Carver; Shuwen Wang; Fengqiu Zhang; Liuling Yan (Theoretical and Applied Genetics, 2009)

Effect of Photoperiod on the Regulation of Wheat Vernalization Genes VRN1 and VRN2 - Jorge Dubcovsky; Artem Loukoianov; Daolin Fu; Miroslav Valarik; Alexandra Sanchez; Liuling Yan (Plant Molecular Biology, 2006)

Large deletions within the first intron in VRN-1 are associated with spring growth habit in barley and wheat - Daolin Fu; Péter Szűcs; Liuling Yan; Marcelo Helguera; Jeffrey S. Skinner; Jarislav von Zitzewitz; Patrick M. Hayes; Jorge Dubcovsky (Molecular Genetics and Genomics, 2005)

Molecular and Structural Characterization of Barley Vernalization Genes - Jarislav von Zitzewitz; Péter Szűcs; Jorge Dubcovsky; Liuling Yan; Enrico Francia; Nicola Pecchioni; Ana Casas; Tony H.H. Chen; Patrick M. Hayes; Jeffrey S. Skinner (Plant Molecular Biology, 2005)

Large deletions within the first intron in VRN-1 are associated with spring growth habit in barley and wheat - Daolin Fu; Péter Szűcs; Liuling Yan; Marcelo Helguera; Jeffrey S. Skinner; Jarislav von Zitzewitz; Patrick M. Hayes; Jorge Dubcovsky (Molecular Genetics and Genomics, 2005)